(3GdMGhj aj TQM bUjOI GdSGhjs - (3eMehO Hf CMeO Hf ehSi Hf CMeO, CHh eMeO, HOQ GdOjf GdYjfj , J (B855 (3g` s; (3YHO Gddg Hf eMeO GdNRQLj, VjGA GdOjf CHh eMeO,J (B626 (3g` s
(3ChdgG (B:s
(3hHYO aEf GdYHO CHG eMeO eMehO Hf CMeO GdYjfj deG QCjJ GdbUjOI GdJi fXegG GdEeGe UOQGdOjf GdSGhj eSei HcJGH GdMGhj aj TQM bUjOI GdSGhj s
(3BNQgG (B:s
(3dCfg HYO gPg GdbUjOI fXe bUjOI CNQi eTJedI Ydi Cda HjJ aj GdYQhV hgPG BNQ ef gPG GdTQM HGdEjVGM s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdYQhV hGdbhGais